1998
DOI: 10.1029/1998gl900059
|View full text |Cite
|
Sign up to set email alerts
|

A system of circumpolar waves in Jupiter's stratosphere

Abstract: Abstract. We report on the optical identification on Hubble Space Telescope (HST) and Voyager 1 archived images, of a circumpolar system of Jovian stratospheric quasi-stationary waves, centered at planetographic latitudes-53%-62 ø, and-67 ø with averaged zonal wavenumbers 23, 11, and 12 respectively. The most conspicuous wave is detected in the 890-nm strong absorption band of methane at -67 ø latitude. Its amplitude changes in a matter of days, stretching and contracting but preserving the number of component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…• S which were marginally detected in previous studies (Sanchez-Lavega et al 1998b, Vincent et al 2000.…”
Section: The Average 1995-1998 Wind Profilementioning
confidence: 71%
“…• S which were marginally detected in previous studies (Sanchez-Lavega et al 1998b, Vincent et al 2000.…”
Section: The Average 1995-1998 Wind Profilementioning
confidence: 71%
“…The rapid alterations of SL-9 impact sites around cyclonic and anticyclonic storms also demonstrate that eddies are efficient transport mechanisms in the lower stratosphere (Simon and Beebe 1996). It is likely that the equatorward projections, or "breaking" waves (Sanchez-Lavega et al 1998), seen in the south polar shading are the circulation patterns that meridionally transport the small particles from the south polar hood into the south polar shading. Similarly, the lobes surrounding the north polar hood would have the same effect in the north.…”
Section: Aerosol Transport By the Zonal Winds And The North-south Asymentioning
confidence: 97%
“…• S, and likely the result of the meridional spreading of the SL-9 debris (Sanchez-Lavega et al 1998). By June 1996, the shading retracted back to 49.7…”
Section: South Polar Shading and South Polar Hoodmentioning
confidence: 97%
“…A visible 'vortex street' may not be apparent in the Cassini images (Sanchez-Lavega et al 2014), but it has been shown previously by analysing the original Voyager images that there was a visible anticyclone and several other non-visible anticyclonic regions aligned centrally along the southern side of the Hexagon edges (Godfrey 1988), but the lack of cyclonic regions to the north exclude it from being the result of a 'vortex street'. The speed needed to propagate the 'vortex street' hexagon in the numerical simulations by Morales-Juberias et al (2011) would exceed the statistical bounds of measurements by Godfrey (1988).…”
Section: Introductionmentioning
confidence: 99%
“…Although the experimental (Barbosa-Aguiar et al 2010) and numerical (Morales-Juberias et al 2011) results produce hexagonal features as a bi-product of a 'vortex street', there remains doubt over the legitimacy of such a model producing the actual North Polar Hexagon on Saturn, due to the debate over the existence of large vortices being observed in the vicinity of the Hexagon region of Saturn (Morales-Juberias et al 2011;Sanchez-Lavega et al 2014). A visible 'vortex street' may not be apparent in the Cassini images (Sanchez-Lavega et al 2014), but it has been shown previously by analysing the original Voyager images that there was a visible anticyclone and several other non-visible anticyclonic regions aligned centrally along the southern side of the Hexagon edges (Godfrey 1988), but the lack of cyclonic regions to the north exclude it from being the result of a 'vortex street'.…”
Section: Introductionmentioning
confidence: 99%